2021
DOI: 10.1007/s41742-021-00324-2
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Cs Removal from Aqueous Solutions by Biochar-Immobilized Potassium Nickel Hexacyanoferrate Prepared Using Ball Mill

Abstract: Biochar-immobilized potassium nickel hexacyanoferrate (KNiFC) as a sorbent for removal of radioactive cesium (Cs) from aqueous solutions was prepared using a novel method. Japanese cedar sawdust loaded with NiSO 4 using a ball mill was carbonized at various temperatures. The resultant Ni-loaded biochar was immersed in a K 4 [Fe(CN) 6 ]•3H 2 O solution, and biochar-immobilized KNiFC was obtained. For comparison, Ni-loaded biochar was also prepared using the impregnation method. The loading of Ni using the ball … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Guo et al (2022) used 3D ZnO modified biochar-based hydrogels for U(VI) elimination, which was easily regenerated and quickly separated after adsorption. Asada et al (2021) reported a biocharimmobilized potassium nickel hexacyanoferrate adsorbent with excellent Cs(I) removal efficiency, which could effectively extract Cs(I) from nuclear waste. Tao et al (2019) found that copper hexacyanoferrate nanoparticle-decorated biochar exhibited a good performance on sedimentation and Cs(I) removal, and the Cs(I) adsorption was homogenous, endothermic and mainly controlled by chemical adsorption.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…Guo et al (2022) used 3D ZnO modified biochar-based hydrogels for U(VI) elimination, which was easily regenerated and quickly separated after adsorption. Asada et al (2021) reported a biocharimmobilized potassium nickel hexacyanoferrate adsorbent with excellent Cs(I) removal efficiency, which could effectively extract Cs(I) from nuclear waste. Tao et al (2019) found that copper hexacyanoferrate nanoparticle-decorated biochar exhibited a good performance on sedimentation and Cs(I) removal, and the Cs(I) adsorption was homogenous, endothermic and mainly controlled by chemical adsorption.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%